Characterization Of Astaxanthinrich Xanthophyllomyces Dendrorhous Extract From A Hyperproducing Mutant And Its Effects On Breast Cancer Cells - Khaw, Shin Yuan (2022)
Astaxanthin is a carotenoid with multiple health benefits including antioxidant and anticancer properties. An astaxanthin-hyperproducing X. dendrorhous mutant was generated due to the growing preference for natural pigment. This work aimed to study the astaxanthin-rich X. dendrorhous extracts and its effect on MCF-7 and MDA-MB- 231 cells. Spectrometric, TLC and HPLC analysis evidenced that mutant M34 produced astaxanthin in higher quantity and purity than the wild type. Mutant astaxanthin extract showed a higher scavenging activity compared to wild type astaxanthin extract in DPPH assay. MTT assays proved that wild type and M34 astaxanthin extracts were not toxic towards the non-cancer origin MCF-10A cells. Wild type and mutant astaxanthin extracts exhibit growth-inhibitory effect in dosedependent manner in MCF-7 and MDA-MB-231 cells. Mutant astaxanthin extract showed a lower IC50 than wild type extract and was more effective in inhibiting both MCF-7 and MDA-MB-231 cells. The IC50 values of wild type and mutant astaxanthin extracts did not exceed the required upper limit of 30 μg/ml.